Pengembangan Video Powtoon Berbasis Saintifik untuk Siswa Kelas V SD Muhammadiyah 8 Surabaya - Deni Adi Putra (Jurnal Bidang Pendidikan Dasar, 2021)
This study aims to produce valid, practical, and effective scientific-based powtoon videos. The development model used in this study is a 4-D model. The results of media validation by material experts are 88%, media experts are 93% with the "Very Eligible" criteria. The practicality of the media is 79% with the “Practical” criteria. And the teacher response questionnaire was 81% with the criteria of "Very Practical". The results of the effectiveness test are 76% of students get scores that meet the KKM. The conclusion of this study is that the product developed has the criteria of being very feasible, very practical, and effective.